Black-legged kittiwakes as messengers of Atlantification in the Arctic - Vihtakari, Mikko; Welcker, Jorg; Moe, Børge; Chastel, Olivier; Tartu, Sabrina; Hop, Haakon; Bech, Claus; Descamps, Sébastien; Gabrielsen, Geir W. (Scientific Reports, 2018)
Climate warming is rapidly altering marine ecosystems towards a more temperate state on the European side of the Arctic. However, this “Atlantification” has rarely been confirmed, as long-term datasets on Arctic marine organisms are scarce. We present a 19-year time series (1982–2016) of diet samples from black-legged kittiwakes as an indicator of the changes in a high Arctic marine ecosystem (Kongsfjorden, Svalbard). Our results highlight a shift from Arctic prey dominance until 2006 to a more mixed diet with high contribution of Atlantic fishes. Capelin, an Atlantic species, dominated the diet composition in 2007, marking a shift in the food web. The occurrence of polar cod, a key Arctic fish species, positively correlated with sea ice index, whereas Atlantic species demonstrated the opposite correlation indicating that the diet shift was likely connected with recent climate warming. Kittiwakes, which gather available fish and zooplankton near the sea surface to feed their chicks, can act as messengers of ecosystem change. Changes in their diet reveal that the Kongsfjord system has drifted in an Atlantic direction over the last decade. publishedVersion © The Author(s) 2018. Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.